Paepalanthus altamirensis, a new species of Paepalanthus subg. Platycaulon (Eriocaulaceae) from Brazil - Tissot-Squalli, Mara L.; Sauthier, Luana J. (Phytotaxa, 2017)
We describe Paepalanthus altamirensis, a new species of Paepalanthus subg. Platycaulon, compare it with other species of the subgenus, and discuss its morphological variation, habitat, and conservation. Paepalanthus altamirensis has red coloration on the adaxial surface of the foliar base, like six other species of the subgenus, but can be easily differentiated by morphological and anatomical features of vegetative and reproductive organs. Paepalanthus altamirensis has a restricted distribution and few mature individuals are known, therefore the species is classified as critically endangered according to the criteria of IUCN.